PENGENDALIAN KUALITAS PRODUKSI GENTENG MENGGUNAKAN PENERAPAN METODE SIX SIGMA DAN FAILURE MODE AND EFFECT ANALYSIS (FMEA) - Erlin Riandari; Joko Susetyo; Endang Widuri Asih (Jurusan Teknik Industri, Institut Sains & Teknologi AKPRIND Yogyakarta, 2022)
Super MD Tile Factory is an individual business that is engaged in the production of tiles in small quantities. One of the products produced is Mantili tile with make to stock and make to order production systems. Defective products in the production process cannot be completely avoided. The company sets a tolerance for defective products in production, which is 4.44%, but in practice the defective products produced can reach 8%. Types of defects such as porous, cracked, broken, cracked tiles, and charred.The work using the six sigma method and Failure Mode and Effect Analysis (FMEA), obtained a DPMO value of 16634 and a sigma value of 3.63. This shows that this value is still far from the world industry level which reaches 6 sigma with a DPMO value of 3.4.Based on the Failure Mode and Effect Analysis (FMEA) method, the calculation of the Risk Priority Number (RPN) value is obtained. Based on the RPN value, the priority causes of errors were obtained, namely, errors when setting the temperature for burning tile 512 RPN, less careful in laying tiles 448 RPN, raw material composition 392 RPN, and errors in taking tiles that were not dry 224 RPN. Suggestions that can be given in an effort to improve the quality of tile products are to add temperature gauge items and check or inspect more frequently during the production process.